Neutron diffraction study of the magnetic-field-induced transition in Mn3GaC - Cakir, O.; Acet, M.; Farle, M.; Senyshyn, A. (AMER INST PHYSICS, 2014)
The antiperovskite Mn3GaC undergoes an isostructural cubic-cubic first order transition from a low-temperature, large-cell-volume antiferromagnetic state to a high-temperature, small-cell-volume ferromagnetic state at around 160 K. The transition can also be induced by applying a magnetic field. We study here the isothermal magnetic-field-evolution of the transition as ferromagnetism is stabilized at the expense of antiferromagnetism. We make use of the presence of the two distinct cell volumes of the two magnetic states as a probe to observe by neutron diffraction the evolution of the transition, as the external magnetic field carries the system from the antiferromagnetic to the ferromagnetic state. We show that the large-volume antiferromagnetic and the small-volume ferromagnetic states coexist in the temperature range of the transition. The ferromagnetic state is progressively stabilized as the field increases. (C) 2014 AIP Publishing LLC.
Keywords: FERROMAGNETIC TRANSITION; Physics